Motor Pathway Injury with Periventricular Leukomalacia and Spastic Diplegia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
The relationship between motor pathway injury and motor impairment was investigated by voxelwise correlation analysis in 43 patients (median age 12 years) with periventricular leucomalacia and spastic diplegia at Yonsei University College of Medicine, Seoul, Korea.